The impact physical distancing during the COVID-19 pandemic on mental health among adolescents: a systematic literature review - Isma Faridatus Sholihah; Ira Nurmala; Muji Sulistyowati; Shrimarti Rukmini Devy (Intelektual Pustaka Media Utama, 2022)
The spread of the coronavirus disesase 2019 (COVID-19) virus is relatively fast and has infected hundreds of countries. The number of people suffering from COVID-19 continues to increase and is increasingly concerning. To reduce the possibility of spreading the Coronavirus, which is easily contagious, the World Health Organization (WHO) advises the public to maintain a safe distance from other people through physical distancing. This study is a systematic review using the preferred reporting item for systematic reviews and meta-analyzes (PRISMA) method using 454 articles from online journal databases. The databases used in the literature search were Pubmed, Science Direct, Sage, Emerald, and Proquest from 2020-2021. Based on the inclusion and exclusion characteristics, there were 8 of 454 articles met the inclusion criteria, and select for in-depth analysis. Physical distancing policy has an impact on adolescent mental health. Some of the mental disorders experienced by adolescents include feeling lonely, anxious, stressed, psychiatric disorders, to emotional disturbances. Boys have a higher increase in mental health problems than girls. We need a social network and social support specifically in adolescents to maintain physical distancing during the adolescent mental health policy in the COVID-19.